Study of mental states and peculiarities of elementary school child's personality with disadaptation - Маркелова, Анастасія; Ніколаєв, Леонід (Київський національний університет імені Тараса Шевченка, 2019)
The authors describe and propose ways to determine the level of school disadaptation. Associated psychological factors are identified: levels of school motivation and adaptation, situational and personal anxiety, indicators and forms of aggression, self-esteem of depression. The obtained experimental data on the tendency to disadaptation are analyzed, as well as the psychological factors that influence the formation of disadaptation of young school children are investigated. Quantitative and qualitative analysis of mental states and personality characteristics of elementary school children with disadaptation shall be conducted to study their school disadaptation, organization of comprehensive psychological and pedagogical assistance to school children, teachers and parents. Existing research methods are mainly based on self-estimation methodologies. Experimental data on addiction to disadaptation was obtained, additionally, the psychological factors, which influence on disadaptation formation of elementary school children, were examined. The majority of examined children were found to have a low level of reactive anxiety and a high level of personal anxiety.

Описано та запропоновано шляхи визначення рівня шкільної дезадаптації. Визначено супутні психологічні чинники: рівні шкільної мотивації та адаптації, ситуативної й особистісної тривожності, показники та форми агресії, самооцінки депресії. Аналізуються отримані експериментальні дані про схильність до дезадаптації, а також досліджено зазначені психологічні чинники, які впливають на формування дезадаптації дітей молодшого шкільного віку.
Дослідження психічних станів та властивостей особистості молодших школярів із ознаками дезадаптації
Keywords: молодші школярі; школа; адаптація; дезадаптація; агресія; тривожність; самооцінка; депресія; почуття; elementary school children; school; adaptation; disadaptation; aggression; anxiety; self-esteem; depression; feelings